Forming A Pedagogue’s Research Competences in Innovative Educational Environment - Yuryevna Tsibizova, Tatyana; Gennadievich Poyarkov, Nikolay; Viktorovna Mamaeva, Svetlana; Vladimirovich Rubtsov, Alexander; Mefodyevna Plekhanova, Elena; Viktorovna Kolchina, Vera; Nikolaevna Tonkavich, Iryna (International Journal of Engineering and Technology, 2018)
Introduction. Changes that take place in different spheres of life in Russia (economic, political, social, cultural) determine new requirements to the goals, values, functions of education in providing the development and self-realization of students. A graduate of a modern school should master a complex of information and research skills, and have critical and creative thinking. Research methodology. The orientation of education towards the growth of a student as a person, bearer of certain individual peculiarities, and activity subject may be of use only if an effective strategy of pedagogic work is developed. Such a strategy should be scientifically grounded on the basic principles of modern approaches implemented in pedagogy and psychology: humanistic, personality-, activity- and competence-oriented. Research results. Four spheres of a pedagogueâ€™s professional activity in an innovative educational environment have been distinguished: sphere of analysis, synthesis and mastering pioneering pedagogic experience; sphere of popularization and initial practical use of pioneering pedagogic experience and advanced developments; sphere of the improvement of professional skills and realization of creative potential of a teacher; sphere of innovative processes in the system of education. Discussion. The essence of a pedagogueâ€™s research activity is conditioned by the functions, which are based on the following factors: optimization of the teaching and educational process; specifically, structured controlled cognitive process; processes of self-improvement, self-instruction and self-education, self-realization; mastering professional pedagogic activity of a new level. Conclusion. Four levels of the development of a teacherâ€™s research competences have been distinguished: basic, empiric (local and initiative), productive (tactical), and constructive (strategic).Â Â